PENGARUH PENERAPAN SISTEM E-FILLING DAN TINGKAT PEMAHAMAN PERPAJAKAN TERHADAP PENERIMAAN PAJAK PENGHASILAN ORANG PRIBADI DENGAN KEPATUHAN WAJIB PAJAK SEBAGAI VARIABEL PEMODERASI (Studi Kasus Pada Wajib Pajak UMKM Di Kecamatan Ilir Timur I) - Kurniawan, Muhammad Orba; Aprianto, Aprianto Apri (Universitas Muhammadiyah Palembang, 2018)
The formulation of the problem in this study was how the influence of E-Filling system application and understanding of taxation level on individuals income revenue tax with taxpayer compliance as moderation variable. The objective of this study was to analyze the influence of E-Filling system application and understanding of taxation level on individuals income revenue tax with taxpayer compliance as moderation variable. The study was asspciative research. The population used in this study was the small and medium sized micro business taxpayer in kecamatan ilir timur I. The sample in this study was 90 respondents. The data collection methods used in this study was questionnaires. The hypothesis tests used were multiple linear regression and moderated resgression analysis. The results of this study showed that partially the application of E-Filling system gave a positive influence on tax revenue, the level of understanding of taxation gave a positive influence on tax revenue, the level of compliance of taxpayers could not moederate the influence of E-Filling application system on tax revenue, and taxpayer compliance could not moderate the influence of tax understanding level of tax revenue. Simultaneously the application of E-Filling system and tax understanding level gave a positive influence on tax revenue